The Creation of a New Morphological Unit in Spanish: Diachronic Study of the Form No - Esquivel Brizuela, Shaila Lisett (2024)
The aim of this paper is to trace the morphologization process that allowed the formation of a prefix from an adverb, both coinciding in the form no. In order to do this, we consider the theory of grammaticalization to analyze a corpus of 794 Spanish words with no-, gathered from different sources from the 13th to the 21st century. The results show the different stages of the change process in which the adverb expanded its contextual distribution, which allowed it to appear before nouns. In this context, the adverb acquires the typical characteristics of a negation prefix, with specific meaning nuances according to the type of noun base it attaches to: total negation for deverbal nouns (no inclusión, ‘non-inclusion’) or partial negation in the case of concrete nouns (no libro, ‘non-book’).